Regression models of individual standard indicators of systolic amplitude wave and length of thigh rheovasography ascending part depending on the characteristics of the body structure in healthy boys and girls with various somatotype from Podilla - Serheta, I. V.; Vysochanskiy, O. V.; Vastyanov, R. S.; Vlasenko, O. V. (Journal of Education, Health and Sport, 2015)
Serheta I. V., Vysochanskiy O. V., Vastyanov R. S., Vlasenko O. V. Регресійні моделі індивідуальних нормативних показників амплітуди систолічної хвилі і тривалості висхідної частини реовазограми стегна в залежності від особливостей будови тіла здорових хлопчиків і дівчаток Поділля різних соматотипів = Regression models of individual standard indicators of systolic amplitude wave and length of thigh rheovasography ascending part depending on the characteristics of the body structure in healthy boys and girls with various somatotype from Podilla. Journal of Education, Health and Sport. 2015;5(8):187-196. ISSN 2391-8306. DOI 10.5281/zenodo.28063 http://dx.doi.org/10.5281/zenodo.28063 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A187-196 https://pbn.nauka.gov.pl/works/607732 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 12.08.2015. УДК: 616-071.3:675.1:611.984:612.655/.656 Регресійні моделі індивідуальних нормативних показників амплітуди систолічної хвилі і тривалості висхідної частини реовазограми стегна в залежності від особливостей будови тіла здорових хлопчиків і дівчаток Поділля різних соматотипів REGRESSION MODELS OF INDIVIDUAL STANDARD INDICATORS OF SYSTOLIC AMPLITUDE WAVE AND LENGTH OF THIGH RHEOVASOGRAPHY ASCENDING PART DEPENDING ON THE CHARACTERISTICS OF THE BODY STRUCTURE IN HEALTHY BOYS AND GIRLS WITH VARIOUS SOMATOTYPE FROM PODILLYA І. В. Сергета, О. В. Височанський, *Р. С. Вастьянов, О. В. Власенко I. V. Serheta, O. V. Vysochanskiy,*R. S. Vastyanov, O. V. Vlasenko Вінницький національний медичний університет імені М. І. Пирогова, м. Вінниця; *Одеський національний медичний університет, м. Одеса Vinnitsa N. I. Pirogov National Medical University, Vinnitsa; *Odessa National Medical University, Odessa Summary In work, based on anthropometric characteristics and somatotypological indicators, using the method of stepwise regression inclusion in urban boys and girls of Podillia with various somatotypes built regression models of amplitude and time parameters rheovasography (RVG) of thighs that are most important in the clinic - systolic wave amplitudes parameters and the length of the ascending part. In boys regression models systolic wave amplitude RVG of thighs with determination coefficient (R2) more than 0,5 built for mesomorph (R2=0,674), ectomorph (R2=0,644) and ecto-mesomorph (R2=0,629), and in girls - for ecto- and ecto-mesomorph (R2=0,611 and 0,866). Models duration of ascending part of RVG thighs in boys built only for ectomorph (R2=0,502), and in girls - for meso- (R2=0,735), ecto- (R2=0,672) and ecto-mesomorph (R2=0,904). Кey words: regression models, rheovasography thighs, healthy adolescents, anthropometry, somatotype. Резюме В роботі на основі особливостей антропометричних та соматотипологічних показників, використовуючи метод покрокової регресії з включенням, у міських хлопчиків і дівчаток Поділля різних соматотипів побудовані регресійні моделі амплітудних і часових показників реовазограми (РВГ) стегна, що мають найбільше значення в клініці – показників амплітуди систолічної хвилі і тривалості висхідної частини. У хлопчиків регресійні моделі амплітуди систолічної хвилі РВГ стегна з коефіцієнтом детермінації (R2) більше 0,5 побудовані для мезоморфів (R2=0,674), ектоморфів (R2=0,644) і екто-мезоморфів (R2=0,629), а у дівчаток – для екто- й екто-мезоморфів (R2=0,611 і 0,866). Моделі тривалості висхідної частини РВГ стегна у хлопчиків побудовані лише для ектоморфів (R2=0,502), а у дівчаток – для мезо- (R2=0,735), екто- (R2=0,672) і екто-мезоморфів (R2=0,904). Ключові слова: регресійні моделі, реовазографія стегна, здорові підлітки, антропометрія, соматотип. Резюме РегресСИОННЫЕ моделИ ИндивИдуальнЫх нормативнЫх показАТЕЛЕЙ амплИтудЫ систолИчЕСКОЙ ВОЛНЫ И ПРОДОЛЖИТЕЛЬНОСТИ вОСХОДЯЩЕЙ части реовазограмМЫ БЕДРА в заВИСИМОСТИ ОТ особЕННОСтей СТРОЕНИЯ тЕла здоровЫх МАЛЬЧИКОВ И дЕвОЧЕК ПодОлЬя рАзнЫх соматотипОв. В работе на основе особенностей антропометрических и соматотипологических показателей, используя метод пошаговой регрессии с включением, у городских мальчиков и девочек Подолья разных соматотипов построены регрессионные модели амплитудных и часовых показателей реовазограммы (РВГ) бедра имеющие наибольшее значение в клинике – показателей амплитуды систолической волны и продолжительности восходящей части. У мальчиков регрессионные модели амплитуды систолической волны РВГ бедра с коэффициентом детерминации (R2) больше 0,5 построены для мезоморфов (R2=0,674), эктоморфов (R2=0,644) и экто-мезоморфов (R2=0,629), а у девочек – для экто- и экто-мезоморфов (R2=0,611 и 0,866). Модели продолжительности восходящей части РВГ бедра у мальчиков построены лишь для эктоморфов (R2=0,502), а у девочек – для мезо- (R2=0,735), экто- (R2=0,672) и экто-мезоморфов (R2=0,904). Ключевые слова: регрессионные модели, реовазография бедра, здоровые подростки, антропометрия, соматотип.